Sensitive two-stage PCR of p53 genomic DNA exons 5-9. - Kusser, W C; Levin, D B; Glickman, B W (Genome Research, 1993)
To assess the status of the tumor suppressor gene p53 from samples with low levels (sub-nanogram amounts) of genomic DNA (e.g., from exfoliated cells, skin, small biopsies, mucosa), a technique based on two successive rounds of PCR was developed. In the first round, a 1.84-kb fragment spanning exons 5-9 was generated using a "touchdown" protocol. After purification by spun-column chromatography, this fragment was used as a template for the amplification of the individual exons 5-9 with inner primer sets specific for the adjacent intronic regions. Using this nested primer approach, several micrograms of each individual exon were obtained starting from as little as 62.5 pg of total genomic DNA. This material proved ideal for future analyses by single-strand conformational polymorphism (SSCP) analysis and DNA sequencing.